IGF2BP2 contributes to thyroid cancer progression by enhancing the stability of m6A-modified CTSH mRNA - Liangpeng Dong; Lingyun Chen; Xiaofen Qi; Qiaochu Lu; Youwei Li; Mengqi Hou (PLoS ONE, 2025)
Background N6-methyladenosine (m6A) is a prevalent RNA modification in eukaryotes that regulates RNA stability and translation. Dysregulated m6A modification is implicated in cancer progression. This study investigated the role of the m6A reader protein, insulin-like growth factor 2 mRNA-binding protein 2 (IGF2 BP2), in the progression of thyroid cancer (TC). Methods Cell proliferation was assessed using cell counting kit-8 (CCK8) and 5-ethynyl-2’-deoxyuridine (EdU) assays. Cell migration and invasion were evaluated by Transwell assays. A xenograft tumor model was employed to examine the impact of IGF2 BP2 on tumor growth in vivo. Gene functional annotation was performed through GO analysis. Spearman correlation analysis was utilized to evaluate the relationship between the expression levels of cathepsin H (CTSH) and IGF2 BP2. RIP-qPCR and RNA pull-down assays were conducted to confirm the interaction between IGF2 BP2 and CTSH mRNA. Results Elevated IGF2 BP2 expression correlated significantly with advanced N stage in TC. Knockdown of IGF2 BP2 inhibited TC cell proliferation, migration, and invasion in vitro, as well as tumor growth in vivo. CTSH expression mirrored IGF2 BP2 expression. IGF2 BP2 interacted with CTSH mRNA, enhancing its stability in an m6A-dependent manner. Overexpression of CTSH counteracted the effects of IGF2 BP2 knockdown on TC cell proliferation, migration, invasion, and epithelial-to-mesenchymal transition (EMT). Conclusion IGF2 BP2 accelerates TC progression by recognizing and stabilizing m6A-modified CTSH mRNA. IGF2 BP2 and CTSH represent potential diagnostic and therapeutic targets for TC.